2017
DOI: 10.1093/gbe/evw290
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Scans across Three Eucalypts Suggest that Adaptation to Aridity is a Genome-Wide Phenomenon

Abstract: Widespread species spanning strong environmental (e.g., climatic) gradients frequently display morphological and physiological adaptations to local conditions. Some adaptations are common to different species that occupy similar environments. However, the genomic architecture underlying such convergent traits may not be the same between species. Using genomic data from previous studies of three widespread eucalypt species that grow along rainfall gradients in southern Australia, our probabilistic approach prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 74 publications
3
31
1
Order By: Relevance
“…These include the first QTL to be detected in eucalypts underlying direct measurements of drought damage and recovery, as well as those for relative lignotuber size, which has been implicated as playing important roles in recovery (Borzak et al, ; Lloret et al, ; Paula & Pausas, ; Walters, Bell, & Read, ). Our results argue that these traits are under multigenic control, with up to four independent QTL detected per trait in this mapping family, consistent with genomic studies that suggest that adaptation to aridity is a genome‐wide phenomenon in eucalypts (Jordan, Hoffmann, Dillon, & Prober, ; Steane et al, ) and other taxa (Eckert et al, ). Although seedling size prior to drought did impact susceptibility to drought damage, as suggested in our first hypothesis, this was mainly evident in the correlations, and the majority of QTL we detected for drought damage and recovery were independent of those for growth (HT1, HT2, and TL).…”
Section: Discussionsupporting
confidence: 90%
“…These include the first QTL to be detected in eucalypts underlying direct measurements of drought damage and recovery, as well as those for relative lignotuber size, which has been implicated as playing important roles in recovery (Borzak et al, ; Lloret et al, ; Paula & Pausas, ; Walters, Bell, & Read, ). Our results argue that these traits are under multigenic control, with up to four independent QTL detected per trait in this mapping family, consistent with genomic studies that suggest that adaptation to aridity is a genome‐wide phenomenon in eucalypts (Jordan, Hoffmann, Dillon, & Prober, ; Steane et al, ) and other taxa (Eckert et al, ). Although seedling size prior to drought did impact susceptibility to drought damage, as suggested in our first hypothesis, this was mainly evident in the correlations, and the majority of QTL we detected for drought damage and recovery were independent of those for growth (HT1, HT2, and TL).…”
Section: Discussionsupporting
confidence: 90%
“…Genotype‐environment association (GEA) studies could detect individual alleles which vary in frequency across some environmental cline, accounting for geography and genome‐wide patterns (as has been observed with reduced‐representation sequencing in related species, e.g. Steane, Mclean, et al, ; Steane, Potts, et al, ; Steane et al, ). Loci that have undergone selective sweeps could also be detected, shedding further light on recent evolution (Nielsen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, if many genes or combinations of genes are adaptive across replicated gradients, there could be substantial flexibility in genetic responses. Studies in three eucalypt species across the SWATT and Victorian Eucalyptus Adaptation Transect (VEAT) have demonstrated that adaptation to climate is a genome‐wide phenomenon involving multiple genes and gene pathways in different species (Steane et al., ). While there has been extensive discussion around theoretical expectations of the predictability of evolution (e.g., Rockman, ), well‐designed transect studies will help resolve this question.…”
Section: Strengthening Transect Researchmentioning
confidence: 99%
“…In this situation, a single transect would inadequately capture the environmental driver of interest (Travis, Brooker, Clark, & Dytham, ). Analyzing data from multiple transects can also disentangle the relative contribution of neutral (e.g., migration—isolation by distance) and adaptive (e.g., selection—isolation by environment) processes to avoid interpreting divergence due to isolation as adaptation (Sexton, Hangartner, & Hoffmann, ; Steane et al., ).…”
Section: Strengthening Transect Researchmentioning
confidence: 99%